Happy 2 Smell (H2S) - Santos, S.; Pereira, A.; Duarte, D.; Fortunato, J. (Open Schools Journal for Open Science, 2020)
A problem was initially identified: the emission of polluting gases into the atmosphere, namely hydrogen sulphide, H2S, by the tanneries close to our school district. After carrying out theoretical investigations in Biology and Chemistry, the students developed an idea for a project, which consisted of creating a biological filter, with a porous matrix that could be easily traversed by the H2S gas, using, for this purpose, the dry fruit of the plant Luffa aegyptiaca. This material possesses a high porosity and good physical and chemical resistance, serving as a support matrix for sulphur bacteria and, initially, also their culture medium. In collaboration with Alcanena's Wastwater Treatment Plant, sludge from different treatment stages containing sulphurous bacteria were collected. These bacteria manage to transform H2S into sulphur and water. Finally, in collaboration with CTIC (Technological Center for the Leather Industry), iodometric titrations were carried out, proving the effectiveness of the produced filter.